Weak Form Market Efficiency of the Johannesburg Stock Exchange: Pre, During and Post the 2008 Global Financial Crisis - Olwetu Fusthane; Kapingura F M (Journal of Economics and Behavioral Studies, 2017)
The importance of the efficiency of the stock market cannot be underestimated, given the critical role the stock market plays through brings together those who demand and supply development finance. It is against this background that this study focused on analysing the weak form efficiency of the Johannesburg Stock Exchange for the period 2005 to 2016 utilising several methodologies which include unit root tests, autocorrelation test and variance ratio. The empirical results from unit root tests indicated that the null hypothesis of a random walk could not be rejected. The same also applied to the autocorrelation test and variance ratio test except for a few instances. Thus irrespective of the few instances which represent the inefficiency of the market, to a greater extent there is evidence of the market being weak form efficient. Thus even though the work done towards ensuring that the market is efficient is commendable, there is need to ensure that further steps are taken to enhance the efficiency of the market. This is, to some extent suggest that investors are able to make abnormal profits from the market.